The socio-environmental crime in the doce river basin: a critical to the market principle - Vieiras, Rosinei Ronconi; Tristão, Martha; Neitzel, Bruna Sepulcri (Sociedade & Natureza, 2018)
The article discusses the developmental and productivist model inserted in the contemporary societies, questioning the very notion of development present today in the majority of these societies. It looks to face to the attempt of homogenization in the ways of life and the very exploratory and mercantilist logic of a system that seeks to impose and penetrate throughout the social composition of the society. It considers relevant to enhance other lifestyles and relationships that opposed to excluding deteriorating model present in the capitalist system. To this end, involved with the problems exposed by the biggest environmental crime of Brazil, occurred in the basin of Doce River, located in the States of Minas Gerais and Espírito Santo.